Reference dosimetry data and modeling challenges for Elekta accelerators based on IROC‐Houston site visit data. Issue 5 (1st April 2018) - Kerns, James R.; Followill, David S.; Lowenstein, Jessica; Molineu, Andrea; Alvarez, Paola; Taylor, Paige A.; Kry, Stephen F.
Abstract : Purpose: Reference dosimetry data can provide an independent second check of acquired values when commissioning or validating a treatment planning system (TPS). The Imaging and Radiation Oncology Core at Houston (IROC‐Houston) has measured numerous linear accelerators throughout its existence. The results of those measurements are given here, comparing accelerators and the agreement of measurement versus institutional TPS calculations. Methods: Data from IROC‐Houston on‐site reviews from 2000 through 2014 were analyzed for all Elekta accelerators, approximately 50. For each, consistent point dose measurements were conducted for several basic parameters in a water phantom, including percentage depth dose, output factors, small‐field output factors, off‐axis factors, and wedge factors. The results were compared by accelerator type independently for 6, 10, 15, and 18 MV. Distributions of the measurements for each parameter are given, providing the mean and standard deviation. Each accelerator's measurements were also compared to its corresponding TPS calculation from the institution to determine the level of agreement, as well as determining which dosimetric parameters were most often in error. Results: Accelerators were grouped by head type and reference dosimetric values were compiled. No class of linac had better overall agreement with its TPS, but percentage depth dose and output factors commonly agreed well, while small‐field output factors, off‐axis factors, and wedge factors often disagreed substantially from their TPS calculations. Conclusion: Reference data has been collected and analyzed for numerous Elekta linacs, which provide an independent way for a physicist to double‐check their own measurements to prevent gross treatment errors. In addition, treatment planning parameters more often in error have been highlighted, providing practical caution for physicists commissioning treatment planning systems for Elekta linacs.